IMPACT OF DIGITAL LITERACY ON THE UTILIZATION OF E-RESOURCES IN MANAGEMENT INSTITUTE LIBRARIES - Priyanka Binzlekar Dr. Sanjay K. Sharma (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Library and information science users have flocked to electronic resources in recent years. In order to fully use the many digital resources offered by university libraries, students must possess strong digital literacy skills. The purpose of the research was to examine how students’ degrees of digital literacy influenced their utilisation of digital resources, as well as the ways in which university libraries can help students become more digitally literate and how they can use digital resources effectively.